Analisis Siyasah Tanfidziyah Terhadap Implementasi Pasal 2 Peraturan Menteri Sosial Republik Indonesia Nomor 1 Tahun 2018 Tentang Program Keluarga Harapan (PKH) - Lola Calecha Nova Rona; Jayusman; Dani Amran Hakim (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the implementation of Article 2 of Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program (Program Keluarga Harapan/PKH) in Sukaraya Urban Village, East Baturaja District, Ogan Komering Ulu Regency, and to examine its conformity with the principles of fiqh siyasah tanfidziyah. This study employed an empirical juridical method with a qualitative approach. Data were collected through in-depth interviews with urban village officials, PKH facilitators, and beneficiary and non-beneficiary communities, supported by relevant documentation. The findings indicate that PKH implementation has not been optimal, particularly in terms of targeting accuracy. An inclusion error was identified, involving three economically capable families who continued to receive assistance, while an exclusion error occurred in five poor families who met the eligibility criteria but had not been registered as beneficiaries. These inaccuracies were primarily caused by delays in updating the Integrated Social Welfare Data (Data Terpadu Kesejahteraan Sosial/DTKS) and the limited authority of urban village officials in verifying and validating beneficiary data. From the perspective of fiqh siyasah tanfidziyah, these conditions indicate that PKH implementation has not fully realized the principles of justice (al-'adl), trust (amanah), and public welfare (maslahah). The findings emphasize the need to strengthen data updating and validation mechanisms to ensure that social assistance is distributed more accurately, equitably, and in accordance with the principles of Islamic governance.